Human resource strategic management at the universities: an indigenous model with an emphasis on the role of organizational structure - Ali Reza Rouhani Ghehsareh; Alireza Manzari Tavakoli; Sanjar Salajegheh; Samaneh Mehdizadeh (Social Determinants of Health, 2022)
Background: This study aimed to study the effect of organizational structure and its dimensions including complexity, centralization and formalization on the strategic human resource management (SHRM).